2013
DOI: 10.1089/ten.tea.2012.0233
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Adipose Stem Cell Trophic Factor Production with Differentiation Medium Components to Regenerate Chondral Defects

Abstract: Recent endeavors to use stem cells as trophic factor production sources have the potential to translate into viable therapies for damaged or diseased musculoskeletal tissues. Adipose stem cells (ASCs) can be differentiated into chondrocytes using the chondrogenic medium (CM), but it is unknown if this approach can optimize ASC growth factor secretion for cartilage regeneration by increasing the chondrogenic factor production, while decreasing angiogenic and hypertrophic factor production. The objective of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…VEGF-A, the major angiogenic factor [78], induces MMP expression in arthritic cartilage and OA [79,80]. Our results for hADSCs in micromass at day 7 are consistent with results obtained by Lee et al [81] on a 5-day monolayer of rat ADSCs which showed Dex, Asc and TGF-β supplementation down-regulate VEGF-A expression compared to NC. Both studies indicate Dex supplementation results in the least expression of VEGF-A.…”
Section: Discussion and Future Studiessupporting
confidence: 91%
“…VEGF-A, the major angiogenic factor [78], induces MMP expression in arthritic cartilage and OA [79,80]. Our results for hADSCs in micromass at day 7 are consistent with results obtained by Lee et al [81] on a 5-day monolayer of rat ADSCs which showed Dex, Asc and TGF-β supplementation down-regulate VEGF-A expression compared to NC. Both studies indicate Dex supplementation results in the least expression of VEGF-A.…”
Section: Discussion and Future Studiessupporting
confidence: 91%
“…The environment in which the tissue regeneration takes place needs to be cleaned of damaged tissue and remodeled, inflammation needs to be allowed and suppressed at the proper stages of healing, and blood vessel formation has to keep up with the regeneration process to allow oxygen and nutrients to reach the metabolically very active bone forming osteoblasts. ASCs can both differentiate towards osteoblasts [22], and form trophic factors that influence the before mentioned processes [19]. As it would make sense that ASCs produce increasingly more trophic factors while healing propagates, we hypothesized that as the differentiation of ASCs progresses hASCs produce more factors associated with processes such as angiogenesis and bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…We found that these factors were expressed at moderate levels when compared to other factors (Table 1). It is possible that the presence of ascorbic acid in our culture medium somewhat diminished VEGFA expression, since it has been shown that ascorbic acid-2 phosphate reduces VEGFA secretion in rat ASCs [19]. Of course Shown are the average BMP-2/control ratios (AESD), of those trophic factors who's expression by ASCs is affected by both substrate type (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hMSCs are able to secrete growth factors depending on the stem cell fate; fibroblast growth factor (FGF) during proliferation (Kim & Ma et al 2013), BMP--2 during osteogenic differentiation (Lee et al 2009;Huang et al 2007) and TGF--β during chondrogenic differentiation (Lee et al 2013;). …”
Section: Ecm Materials Directing Stem Cell Behaviourmentioning
confidence: 99%